ECONOMIC DIVERSIFICATION IN GCC COUNTRIES AND THE OPTIMALITY OF A MONETARY UNION - Olga Marzovilla (European Scientific Journal, ESJ, 2014)
The paper examines the capacity of the GCC countries to bear the costs of monetary unification in the light of the indications arising from the traditional optimum currency area theory and in the contest of the deep structural changes that characterize their economies. The author argues that the conditions ensuring the success of a single currency are still lacking in the GCC countries and that the specialization patterns ongoing in their economies increase the risk of asymmetric shocks. In addition, these patterns can affect their ability to deal with the same shocks and, in particular, the ones arising from the exchange rate regime adopted. The paper, therefore, concludes that the GCC countries should introduce an exchange rate system which is best suited to their new economic realities and this need can arise both in the case that they introduce the single currency, and in the case that they retain their national currencies. A basket peg, which includes the most commonly used currencies in their international trade, is considered the best exchange system for these countries.